Frequency and risk factors of internet addiction in medical students: a cross-sectional study - Amina Ehsan; Farwa Iqbal; Muhammad Azeem Rao (Journal of the Pakistan Medical Association, 2021)
Abstract Objectives: The objectives of the study were to find out the prevalence of internet addiction and to determine the risk factors associated with internet addiction in medical students. Methods: This descriptive cross-sectional study was carried out at Rawalpindi Medical University, Rawalpindi from July 2018 to August 2019. Our study population included medical students from all the years of MBBS aged 18-25 years, who have been using the internet for the past two years or more. A Stratified random sampling technique was used. Seventy-six self-administered questionnaires were distributed in each year. Data was entered and analyzed using the Statistical Package for Social Sciences (SPSS version 25). Results: Out of the total sample of 380, the prevalence came out to be 90% (n=342). Two hundred and twenty-two 222 (58.4%) had mild, 115 (30.3%) had moderate, six (1.6%) had severe and 37 (9.7%) had no addiction. Out of the risk factors online friendships (p= 0.007), online relationships (P=0.035), online chatting (p= 0.009), online shopping (p= 0.009), online games (p=0.023) and online series/movies (p< 0.000) were statistically significant. Conclusion: The prevalence of internet addiction is high among medical students, which is mostly of a mild type. Internet addiction is more common in males and non-hostel residents. Other significant risk factors are online relationships, online gaming, and online series/movies. Keywords: Prevalence, internet, medical students, risk factors. Continuous...